2018
DOI: 10.1002/anie.201802834
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst‐Dependent Chemoselective Formal Insertion of Diazo Compounds into C−C or C−H Bonds of 1,3‐Dicarbonyl Compounds

Abstract: A catalyst-dependent chemoselective one-carbon insertion of diazo compounds into the C-C or C-H bonds of 1,3-dicarbonyl species is reported. In the presence of silver(I) triflate, diazo insertion into the C(=O)-C bond of the 1,3-dicarbonyl substrate leads to a 1,4-dicarbonyl product containing an all-carbon α-quaternary center. This reaction constitutes the first example of an insertion of diazo-derived carbenoids into acyclic C-C bonds. When instead scandium(III) triflate was applied as the catalyst, the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(51 citation statements)
references
References 60 publications
1
47
0
3
Order By: Relevance
“…The aryl ester moiety of the diazoesters plays a key role in the unusual chemoselectivity, and the addition of a Brønsted acid to the reaction mixture improves the yield of the C−C bond insertion product. While we were preparing this manuscript, Bi and co‐workers reported an elegant AgOTf‐catalyzed C−C bond insertion reaction of 2‐aryl‐2‐diazoacetates with aryl 1,3‐diketones 2 (where R 1 or R 2 is an aryl group). Compared with this silver‐catalyzed system, our gold‐catalyzed system exhibits higher activity (reaction time: 1 h for gold versus 6 h for silver; catalyst loading: as low as 0.5 mol % for gold versus 10 mol % for silver) and can be extended to alkyl 1,3‐diketones (where R 1 , R 2 , or both are alkyl).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aryl ester moiety of the diazoesters plays a key role in the unusual chemoselectivity, and the addition of a Brønsted acid to the reaction mixture improves the yield of the C−C bond insertion product. While we were preparing this manuscript, Bi and co‐workers reported an elegant AgOTf‐catalyzed C−C bond insertion reaction of 2‐aryl‐2‐diazoacetates with aryl 1,3‐diketones 2 (where R 1 or R 2 is an aryl group). Compared with this silver‐catalyzed system, our gold‐catalyzed system exhibits higher activity (reaction time: 1 h for gold versus 6 h for silver; catalyst loading: as low as 0.5 mol % for gold versus 10 mol % for silver) and can be extended to alkyl 1,3‐diketones (where R 1 , R 2 , or both are alkyl).…”
Section: Methodsmentioning
confidence: 99%
“…More importantly, we found that even aliphatic 1,3‐diketones underwent C−C bond insertion reactions with good yields ( 3 aq – 3 as , 70–79 % yield). It is worth noting that the AgOTf‐catalyzed reaction of methyl 2‐diazo‐2‐phenylacetate with a typical aliphatic 1,3‐diketone ( 2 q ) under the optimal conditions described by Bi and co‐workers gave a poor yield (18 %) of the C−C insertion product. The structure of 3 ab was confirmed by means of single‐crystal X‐ray analysis…”
Section: Methodsmentioning
confidence: 99%
“…α‐Diazo monocarbonyl compounds have attracted considerable attention due to their high reactivity and wealth of possible synthetic transformations . Today, however, certain such compounds remain poorly explored.…”
Section: Introductionmentioning
confidence: 99%
“…The intermolecular carbene insertion into the electron‐deficient C−H bonds is more challenging, and the chemoselectivity of reaction using copper or dirhodium catalysts is poor . Quite recently, several gold catalysts, copper catalysts, scandium catalysts, diene‐Rh(I) catalysts were developed for the intermolecular carbene insertion into the C−H bonds of 1,3‐diketones, cyclic lactones and β‐ketoesters. The known catalysts for carbene insertion into electron‐deficient C−H bonds are highly substrate dependent.…”
Section: Methodsmentioning
confidence: 99%